Use of auxiliary techniques for assessing the reproductive capacity of natural service Nellore bulls - Fernandes, Luana Gomes [UNESP]; Borges, Marcelo Sant'Ana [UNESP]; de Oliveira Silva, Marina [UNESP]; Rodrigues, Naiara Nantes [UNESP]; Vicentini, Rogério Ribeiro; Crespilho, André Maciel; Mercadante, Maria Eugênia Zerlotti; Monteiro, Fabio Morato [UNESP] (Elsevier, 2022)
The aim of this study was to investigate whether parameters obtained by computer-assisted sperm analysis (CASA), infrared thermography (IRT), and testicular B-mode and Doppler ultrasound can be used as indicators of fertility in natural service Nellore bulls. Twenty-nine Nellore bulls were evaluated on days 66 (-D66), 38 (-D38), and 10 (-D10) before the beginning of natural service mating. In all assessments, semen samples were collected and sperm kinetics were evaluated by CASA, thermographic imaging of the scrotal and ocular region, testicular B-mode ultrasound, and Doppler ultrasound of the spermatic cord. At the end of natural service, the bulls were classified based on the pregnancy rate of individual batches into low fertility (pregnancy rate 66.57 ± 0.62 %), medium fertility (76.47 ± 0.51 %), and high fertility (84.80 ± 0.60 %) groups. No difference in the IRT parameters was observed between groups. High fertility animals exhibited higher average path velocity (VAP = 110.98 µm/s), straight line velocity (VSL = 87.05 µm/s), curvilinear velocity (VCL = 190.78 µm/s), pulsatility index (PI = 0.93), and resistive index (RI = 0.57) than low fertility animals (VAP = 100.02 µm/s; VSL = 79.84 µm/s; VCL = 173.22 µm/s; PI = 0.69; RI = 0.48). Positive correlations were observed between pregnancy rate and VSL (0.21), PI (0.28) and RI (0.32). In conclusion, IRT does not provide fertility indicators in Nellore bulls. The VAP, VSL and VCL obtained by CASA and PI and RI obtained by Doppler ultrasound can be used as indicators of fertility in Nellore bulls.
Keywords: CASA; Fertility; Infrared thermography; Semen; Ultrasound